Comparison of patient-reported outcomes during acute exacerbations of chronic obstructive pulmonary disease. Issue 1 (9th October 2018) - Nishimura, Koichi; Nakamura, Saya; Kusunose, Masaaki; Nakayasu, Kazuhito; Sanda, Ryo; Hasegawa, Yoshinori; Oga, Toru
Abstract : Introduction: The aim of this study was to investigate which patient-reported outcome measure was the best during the recovery phase from severe exacerbation of chronic obstructive pulmonary disease (COPD). Methods: The Exacerbations of Chronic Pulmonary Disease Tool (EXACT), the COPD Assessment Test (CAT), the St George's Respiratory Questionnaire (SGRQ), the Dyspnoea-12 (D-12) and the Hyland Scale (global scale) were recorded every week for the first month and at 2 and 3 months in 33 hospitalised subjects with acute exacerbation of COPD (AECOPD). Results: On the day of admission (day 1), the internal consistency of the EXACT total score was high (Cronbach's alpha coefficient=0.89). The EXACT total, CAT, SGRQ total and Hyland Scale scores obtained on day 1 appeared to be normally distributed. Neither floor nor ceiling effects were observed for the EXACT total and SGRQ total scores. The EXACT total score improved from 50.5±12.4 to 32.5±14.3, and the CAT score also improved from 24.4±8.5 to 13.5±8.4 during the first 2 weeks, and the effect sizes (ES) of the EXACT total and CAT score were −1.40 and −1.36, respectively. The SGRQ, Hyland Scale and D-12 were less responsive, with ES of −0.59, 0.96 and −0.90, respectively. Discussion: The EXACT total and CAT scores are shown to be more responsive measures during the recovery phase from severe exacerbation. Considering the conceptual framework, it is recommended that the EXACT total score may be the best measure during the recovery phase from AECOPD. The reasons for the outstanding responsiveness of the CAT are still unknown.